Induced civic pride and integration - Bernd Süssmuth; Malte Heyne; Wolfgang Maennig (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper investigates whether a nation's contingent value of hosting a mega-event depends on past experience with implied public goods benefits for its residents. Applying data from an ex-ante and ex-post query based on contingent valuation methods, we use the FIFA World Cup 2006 as a natural experiment. The significant ex-post increase in valuation is shown to be due to adventitious citizens requiring an involving experience, rather than to an updating of a prior assessment. The World Cup finals were the first mega-event hosted by reunified Germany. We use this landmark event in German contemporary history to investigate how the integration of the two parts of Germany progressed after 18 years of reunification. We still find a profound difference in clear-sighted civic awareness of East and West German individuals. However, civic pride induced by collective experience can considerably accelerate the convergence of East Germans' preferences towards those of West Germans, which Alesina and Fuchs-Schündeln (2007) recently calculated to take 20 to 40 years or one and a half generation.
Keywords: H49; H59; L83; 330; Experience goods; contingent valuation; civic awareness; German reunification; Ethnopsychologie; Großveranstaltung; Fußballsport; Willingness to pay; Vergleich; Alte Bundesländer; Neue Bundesländer; Deutschland